دلالة ألفاظ الرثاء في شعر طالب الحيدري ملحمة كربلاء أنموذجاً - هادي سلمان, حيدر (Al-Adab Journal, 2018)
Denote the words of Lamentations in the poet Taleb Al- Haidari-epic of Karbala model- Lament Old Art of the oldest literary arts that We received . And the issue of Al- Hussein ( peace be upon him)of the issues that stop then poets ,talked about the Mratijm They described the meanings of heroism and courage, generosity, and inherited the meanings. Haidari and poet of poets Who stood at this issue , depicting the timeless epic best poetic images , and We discussed this indication studying the words of lamentation used by the poet in a poem that lamented by lmam Hussein ( peace be upon him ) is flanked by the timeless epic .